2007
DOI: 10.2478/v10001-007-0021-5
|View full text |Cite
|
Sign up to set email alerts
|

Ototoxicity of Organic Solvents - From Scientific Evidence to Health Policy

Abstract: The scientific workshop, organized under the 6th European Framework Programme, the Marie Curie Host Fellowship for the Transfer of Knowledge "NoiseHear" Project, by the Nofer Institute of Occupational Medicine (Łódź, Poland, 15-16 November 2006), gathered world specialists in noise, chemicals, and ototoxicity, including hearing researchers, toxicologists, otolaryngologists, audiologists and occupational health physicians.The workshop examined the evidence and the links between isolated exposure to organic solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 39 publications
0
41
0
4
Order By: Relevance
“…Several animal studies have confirmed that exposure to combinations of some solvents (mixtures of solvents) will contribute to greater hearing loss than it was found in single-solvent exposures [49][50][51][52][53]. The human studies have also confirmed such results [35]. The assessment of dose-response relationships are usually challenging and demanding.…”
Section: Ijomeh 2017;30(4)mentioning
confidence: 51%
See 3 more Smart Citations
“…Several animal studies have confirmed that exposure to combinations of some solvents (mixtures of solvents) will contribute to greater hearing loss than it was found in single-solvent exposures [49][50][51][52][53]. The human studies have also confirmed such results [35]. The assessment of dose-response relationships are usually challenging and demanding.…”
Section: Ijomeh 2017;30(4)mentioning
confidence: 51%
“…Previous epidemiological studies, indicate that an observed additive or even synergistic effect occurs from having combined exposures to noise and organic solvents mixture, by 2 to 11 times increase in the odds ratio of hearing loss [20][21][22][23][24][25][26]28,31]. It has been demonstrated that there is a synergistic causal effect caused by concurrent exposure to organic solvents mixture and noise in animal models [35]. However, in the case of human studies, the possible synergism of combined exposure to solvents and noise on hearing has not been consistently identified [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although none of the ingredients listed on the MSDS that were given to us had been observed as ototoxicants, users should be aware that moderate exposures (below or around the OEL) to solvents such as toluene [Morata et al 1993;Chang et al 2006], xylene, and mixtures of solvents [Sliwinska-Kowalska et al 2004;Fuente et al 2009] have been shown to be associated with hearing loss [Sliwinska-Kowalska et al 2007]. …”
Section: Results and Discussion (Continued) Ototoxinsmentioning
confidence: 99%